Faktor-Faktor yang Mempengaruhi Kinerja Karyawan melalui Motivasi - Shifa Rihadatul ‘Ays (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Employee performance is something that an agency needs to achieve its goals. Employee performance can also be referred to as a measure of the extent to which an employee or individual succeeds in achieving the goals and standards set by the company itself. Employee ability is a determining factor in whether an employee can carry out their duties properly. Several problems related to employee performance in an agency include ability, discipline and work facilities. This research combines the variables above with research through questionnaires and data processing using the SmartPLS application. Based on the results of this research, it was found that Ability (X1), Work Environment (X2), Work Facilities (X3) have a positive effect on Employee Performance (Y1) and Work Motivation (Y2).